2014
DOI: 10.1111/1574-6968.12516
|View full text |Cite
|
Sign up to set email alerts
|

Changes in metabolome and in enzyme activities during germination ofTrichoderma atrovirideconidia

Abstract: The aim of this work was to study the metabolic changes during germination of Trichoderma atroviride conidia along with selected marker enzyme activities. The increase in proteinogenic amino acid concentrations together with the increase in glutamate dehydrogenase activity suggests a requirement for nitrogen metabolism. Even though the activities of tricarboxylic acid cycle enzymes also increased, detected organic acid pools did not change, which predisposes this pathway to energy production and supply of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Qualitative analysis of main constituents of ginger extract was measured using nuclear magnetic resonance (NMR) according to Kaliňák et al (2014). Briefly, 1 H-NMR spectra were run on a 600 MHz NMR spectrometer (Agilent) equipped with indirect detection probe.…”
Section: Determinations Of Main Constituents Of Ginger Extract Using mentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative analysis of main constituents of ginger extract was measured using nuclear magnetic resonance (NMR) according to Kaliňák et al (2014). Briefly, 1 H-NMR spectra were run on a 600 MHz NMR spectrometer (Agilent) equipped with indirect detection probe.…”
Section: Determinations Of Main Constituents Of Ginger Extract Using mentioning
confidence: 99%
“…Determinations of main constituents of studied extract were done by NMR analysis according to Kaliňák et al (2014).…”
Section: Determinations Of Main Constituents Of Ginger Extract Using mentioning
confidence: 99%
“…Analyses of turmeric sample using NMR spectroscopy Determination of main constituent of the studied extract was done by NMR analysis according to Kaliňák et al (2014) 1 H-NMR standard spectra were measured and compared with the reference spectra published by Payton et al (2007) that confirmed the presence of curcumin (Fig. 1) in the turmeric extract (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Qualitative analysis of curcuminoids presented in obtained turmeric extract was measured by nuclear magnetic resonance (NMR) according to Kaliňák et al (2014). Briefly, 1 H-NMR spectra were run on a 600 MHz NMR spectrometer (Agilent) equipped with indirect detection probe.…”
Section: Analyses Of Turmeric Sample Using Nmr Spectroscopymentioning
confidence: 99%
“…We added the extracts (0.1% and 0.01%) to a suspension of 1 × 10 5 conidia/mL of B. cinerea incubated for 2 h in Sabouraud broth. The suspension was re-incubated for 12 h, and at the end of the period, the lengths of the germ tubes were estimated by digital image analysis (40×) [37]. Treatments were evaluated in triplicate, for a total of 20 units per repetition (N = 60).…”
Section: Effect On Germ Tube Developmentmentioning
confidence: 99%